Model for national legislation to give the Customs powers to implement the agreement on trade-related aspects of intellectual property rights (World Customs Organisation BrusselsBE)
Seeks to provide the Customs administration of members ofthe World Customs Organization with a tool for transposing the Customs-related provisions of the TRIPS Agreement into their own national legislation covering the implementation of that Agreement.
DC